1977
DOI: 10.1530/jrf.0.0510351
|View full text |Cite
|
Sign up to set email alerts
|

Short-latency effect of testosterone on copulatory behaviour and ejaculation in sexually experienced intact male rats

Abstract: The effect of a single injection of testosterone on the number of stimuli required to trigger ejaculation and on copulatory behaviour was investigated in sexually experienced intact male rats. An intraperitoneal injection of 100 microgram free testosterone 1 h before testing facilitated the copulatory behaviour and decreased the number of mounts and intromissions needed for ejaculation; the latter effect was obtained in a test in which a constant interval was kept between each intromission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Although this confound was acknowledged and discounted, the testosterone treatment nonetheless could have affected estradiol responsiveness but not vice versa. The ineffectiveness of testosterone, compared to the previous study [49], may have been due to the males' castrated status.…”
Section: Copulatory Behaviormentioning
confidence: 55%
See 1 more Smart Citation
“…Although this confound was acknowledged and discounted, the testosterone treatment nonetheless could have affected estradiol responsiveness but not vice versa. The ineffectiveness of testosterone, compared to the previous study [49], may have been due to the males' castrated status.…”
Section: Copulatory Behaviormentioning
confidence: 55%
“…Consistent with these shortened latencies being caused by testosterone, gonadally intact male rats injected i.p. with 100 μg of testosterone (simulating a testosterone pulse) exhibited shortened intromission and ejaculation latencies 1 hr after injection [49].…”
Section: Copulatory Behaviormentioning
confidence: 99%
“…However, a short-latency effect of testosterone on copulatory behavior occurs when testosterone is applied to intact male rats [47] . The ineffectiveness of testosterone in the study of Cross and coauthors might have been due to the castrated status of the males.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism of the behavioral effects of such rapid hormonal changes has not been identified. It has been shown that an injection of testosterone given to a sexually experienced and intact male rat one hour before he was allowed to copulate with a female decreased the inter-intromission interval and facilitated ejaculation [157]. Similarly, testosterone also affects penile reflexes of rats in a rapid manner (within 6 to 30 min; [218]).…”
Section: Gonadal Production Of Steroidsmentioning
confidence: 99%